Efficiency comparison of mobile application frameworks for programming using internet technologies - Martyna, Marcin; Smołka, Jakub (Journal of Computer Sciences Institute, 2018)
Over the last few years many frameworks allowing programming mobile applications have been created. Some of them are based on programming languages typical for internet application programming - HTML or JavaScript for example. This paper presents a comparison of three cross-platform environments: PhoneGap, NativeScript and Appcelerator. Using each of these environments an application with identical functionalities was created. The application was designed for Android operating system. Implemented tests allowed for determining which one of the application framework is the most efficient with respect to the time needed for executing respective functions. Obtained results are shown and analyzed.